The moon of the alligators - George, Jean Craighead, 1919-; Rothman, Michael (New York, NY : HarperCollins, 1991)
Describes an alligator's desperate search for food in the Florida Everglades during the month of October.
Includes bibliographical references (p. 47) and index.
Children's Catalog (Wilson)
School Library Journal
6.3
3-6
Keywords: Alligators -- Juvenile literature; Alligators -- Florida -- Everglades -- Juvenile literature; Alligators -- Florida -- Everglades; Alligators